Contribution à L’étude sur la lutte biologique à l’égard de Phyllocnistis citrella Stainton (Lepidoptera ; Gracillariidae), mineuse des Citrus. - SAIAH Farida (My University, 2014)
Phyllocnistis citrella Stainton is responsible for spectacular damage to seedlings (nursery or field) of citrus in Algeria. It induces indirectly behind the fruit set and consequently the production and profitability of the crop. Lifestyle endophyte of insect larva complicated chemical control, thus the use of alternative control becomes indispensable. For this, we have proposed to actively seek strains of microorganisms with pathogenicity may contribute in the regulation of insect populations. Our study is to isolate and identify bacterial and fungal strains naturally present on the insect. The isolation made from nymphs Phyllocnistis citrella who have not completed their life cycle, showed the existence of five different bacterial strains. Identification by the API system shows that the genus Bacillus is the most frequently encountered; it is Aneurinbacillus aneurinlyticus, Bacillus subtilis, Bacillus mycoides, Brevibacillus agri (Bacillus agri) and Bacillus lentus. The pathogenicity test with bacteria isolated showed a significant mortality of larvae of P. citrella, Bacillus mycoides Aneurinbacillus aneurinilyticus, et Bacillus subtilis caused 70%, 75 % and 80 % mortality, respectively. However Brevibacillus agri and Bacillus lentus not have caused 30 to 50%. The isolation from dead nymphs Phyllocnistis citrella (Hemiptera: Aphididae) showing natural symptoms of fungal entomopathogens, revealed the presence of three (03) entomopathogenic strains namely Metarhizium anisopliae var anisopliae, Fusarium semitectum and Aspergillus flavus. The test results of pathogenicity showed that Fusarium semitectum seems fastest to control larvae and eggs of P. citrella and more efficient, with an LD50 of 10 2,13 spores / ml and 10 2,01 spores/ ml. The isolation of fungi from Schistocerca gregaria revealed also the presence of three (03) fungi known for their pathogenicity to different orders of insects namely Metarhizium anisopliae var acridum, Metarhizium flavoviride var minus. Test the effect of the fungus showed that M. flavoviride var minus, is most effective against larvae the eggs of P. citrella, with an LD50 of 101,64spores/ml and 10 2, 36 spores/ml. In the light of these results, we can say that all bacteria and fungi tested were able to effectively divert the defense strategy Phyllocnistis citrella and therefore represent potential microbial control agents against this insect.
Keywords: Phyllocnistis citrella , Citrus sp. , Entomopathogenic bacteria, fungi